Layered double hydroxide nanoparticles to enhance organ-specific targeting and the anti-proliferative effect of cisplatin1. Issue 17 (7th May 2015) - Kuo, Yue-Ming; Kuthati, Yaswanth; Kankala, Ranjith Kumar; Wei, Pei-Ru; Weng, Ching-Feng; Liu, Chen-Lun; Sung, Ping-Jyun; Mou, Chung-Yuan; Lee, Chia-Hung
<x xml:space="preserve">Abstract</x> The role of nanoparticle charge in biodistribution is evaluated by modifying the external surface of layered double hydroxides with various charges and a fluorescent dye (Cy5.5) is doped to assess the biodistribution.